A simple solution for the flavor question - Pisano, Felice [UNESP] (My University, 1996)
We consider a simple way of solving the flavor question by embedding the three-family standard model in a semisimple gauge group extending minimally the weak isospin factor. Quantum chiral anomalies between families of fermions cancel with a matching of the number of families and the number of color degrees of freedom. Our demonstration shows how the theory leads to determination of families structure when the standard model is the input at low energies. The new physics is limited to start below a few TeVs within the reach of the next generation colliders.